The Effect of Artificial Intelligence Adoption, Machine Learning, and AI Ethics on Product Innovation in Start-ups in Bogor - Afrizal, Afrizal; Hildawati, Hildawati; Rifky , Sehan; Vandika, Arnes Yuli (Westscience Press, 2024)
This research investigates the influence of artificial intelligence (AI) adoption, machine learning (ML) integration, and AI ethics on product innovation within Bogor's startup ecosystem. A quantitative approach was employed, collecting data through an online survey from 180 startups. Structural equation modeling with Partial Least Squares (PLS) 3 was utilized for data analysis. The results reveal significant positive relationships between AI adoption, ML integration, AI ethics, and product innovation. AI adoption and ML integration positively impact product innovation, while adherence to ethical AI practices also plays a crucial role. These findings highlight the importance of leveraging AI technologies responsibly and ethically to drive innovation within startup ecosystems. Policymakers, entrepreneurs, investors, and other stakeholders can utilize these insights to foster a conducive environment for sustainable growth and innovation in Bogor's startup community.